Chrysin Attenuates the NLRP3 Inflammasome Cascade to Reduce Synovitis and Pain in KOA Rats - Liao T; Ding L; Wu P; Zhang L; Li X; Xu B; Zhang H; Ma Z; Xiao Y; Wang P (Dove Medical Press, 2020)
Taiyang Liao1– 3*, Liang Ding1,2 *, Peng Wu1– 3*, Li Zhang,1– 3 Xiaochen Li,1– 3 Bo Xu,1– 3 Haosheng Zhang,1– 3 Zhenyuan Ma,1– 3 Yancheng Xiao,1– 3 Peimin Wang1,2 1Department of Orthopedics, The Affiliated Hospital of Nanjing University of Chinese Medicine, Nanjing, Jiangsu 210029, People’s Republic of China; 2Jiangsu Province Hospital of Chinese Medicine, Nanjing, Jiangsu 210029, People’s Republic of China; 3Key Laboratory for Metabolic Diseases in Chinese Medicine, First College of Clinical Medicine, Nanjing University of Chinese Medicine, Nanjing, Jiangsu 210029, People’s Republic of China*These authors contributed equally to this workCorrespondence: Peimin WangDepartment of Orthopedics, The Affiliated Hospital of Nanjing University of Chinese Medicine, No. 155 Hanzhong Road, Qinhuai District, Nanjing, Jiangsu 210029, People’s Republic of ChinaTel +86 15279703634Email drwpm@163.comPurpose: Our recent reports have revealed that inhibiting NLRP3 activation reduces synovial inflammation and fibrosis in knee osteoarthritis (KOA). Synovial inflammation is involved the entire process of KOA and promotes the progression of KOA. Natural flavonoid Chrysin from Scutellariae Radix, a traditional Chinese medicine, exhibits multifarious biological activities and potentially has protective activity against osteoarthritis. However, the mechanism of Chrysin in the treatment of synovial inflammation remains elusive. The purpose of our research was to explore the anti-inflammatory effects of Chrysin on KOA, which was induced by monoiodoacetic acid (MIA) in rats by targeting the NLRP3 inflammasome in the hopes of identifying an effective drug to treat KOA.Methods: The MIA-induced KOA model was used to evaluate the cold pain threshold and paw withdrawal threshold (PWT) of joints after MIA (40 mg/mL) injection into the knee joints. Microscopically, we used LPS (5 ug/mL) and ATP (4 mmol/L) to stimulate fibroblast-like synovial cells (FLSs) to explore the underlying mechanisms and effects of Chrysin. Two staining methods, H&E and Sirius Red, were applied to assess histopathological changes in synovial membranes. Cellular signal transduction was determined by qRT-PCR and WB. Cytokine expression (inflammatory cytokines and pain-related cytokines) was detected by ELISA. The degree of chronic inflammatory pain was evaluated by c-Fos immunofluorescence.Results: The results showed that Chrysin not only attenuated synovial inflammation but also reduced the secretion of pain-related factors and increased the PWT and cold pain threshold in rats. Chrysin also inhibited NLRP3 inflammasome activation and increased IL-1β levels to alleviate the synovitis.Conclusion: Chrysin can relieve knee synovial inflammation and improve pain behavior in KOA rats, which may be related to the ability of Chrysin to inhibit NLRP3 inflammasome activation. Therefore, Chrysin may be developed as a new drug for the treatment of KOA.Keywords: KOA, Chrysin, synovitis, pain, NLRP3 inflammasome